POTENSI KELEMBAGAAN LOKAL DALAM PENGELOLAAN HUTAN MANGROVE DI DESA PANTAI BAHAGIA BEKASI - Metkono , Elfis; Salampessy, Mesalina L; Lidiawati , Ina (Jurnal Nusa Sylva, 2022)
Limited community knowledge about the functions and benefits of mangrove ecosystems, as well as management and utilization without regard to sustainability, causes damage to mangrove ecosystems, as a result logging for the conversion of mangrove land into pond land continues to increase. Community institutions in efforts to preserve mangrove forests have an important role, therefore, this study aims to analyze the potential for local institutional support in mangrove forest management. The sampling method is based on the analysis of key figures of communities involved in mangrove forest management. The data collection method was conducted by in-depth interviews of 30 respondents and the analysis used in this study was qualitative descriptive analysis. The results of the study explained that the situation shows that some mangrove forests have been damaged and community activities are still concentrated on pond processing. The structure shows that the authority in mangrove forest management is specifically regulated by the village government and Perum Perhutani while community groups as partners. Behavior illustrates that the community has access to the utilization of mangrove forest potential for both food and board processing, and performance shows that the use of mangrove forests is still limited to processing fruit for food needs